Menjalajahi Era Baru Teknologi Informasi: Tren dan Tantangan Yang Akan Dihadapi - Muhammad Angga Saputra; Riza Fahlapi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
. The new era of information technology brings significant challenges and trends, impacting corporate performance, social interactions, and education. This research highlights key trends such as artificial intelligence, quantum computing, blockchain technology, Internet of Things, and 5G technology. Through literature studies and qualitative descriptive data analysis, the research results show the positive impact of using information technology in increasing company value, enriching social interactions, and improving the quality of education. However, challenges such as cyber security, technology adoption, resource constraints and regulatory changes need to be addressed. In conclusion, adaptation and innovation are the keys to maximizing the benefits of the new era of information technology, with collaboration between government, industry and society.